INTEGRATING A SET OF LEAN CONSTRUCTION TECHNOLOGY TO BUILDING INFORMATION MODELLING - AL-SARRAY, IHSAN ALI HUSSEIN; SAEED, YOUSIF SALAM; NAJI, AHMED ADIL (Journal of Duhok University, 2020)
Technology has a great impact in managing and implementing highly desired complicate design construction projects, this paper attempted to address a set of synergies between Lean Construction Technologies (LCTs) and Building Information Modeling (BIM) to provide the researchers with a fully comprehensive idea about the impotence of the integration. Through reviewing and presenting of the published papers which presented the integration of one or two lean technology concepts integrated to building information modeling in accordance to the studied cases in one paper, this paper will provide the researcher, developer, and constructing companies with many studied cases presented some of the most important Lean technologies in this field. These technologies are; Last Planer System (LPS); KanBIM; VisiLean; Just-In-Time (JIT); Value Stream Mapping (VSM). Also, this paper suggested the possibility of integrating a 5S technology to BIM for a future study.